Student’s Speaking Problems in Online Learning: A Systematic Research Review - Musleh Fajri; Rohmani Nur Indah (Tell : Teaching of English Language and Literature Journal, 2022)
This study used a systematic review, namely the research process by identifying previous research. Furthermore, this research applies a systematic analysis method that identifies the literature available on Google Scholar. This method has been used to produce original research as well as help researchers to critically analyze, evaluate and synthesize complex ideas. The five phases of systematic literature review are: 1) Framing questions for review 2) Relevant work 3) Assessing study quality 4) Summarizing the evidence 5) Interpret findings. From the results of the review a description it can be understood that there are student problems; they first have difficulty in terms of grammar, vocabulary, pronunciation. However, they also have problems in their psychology in learning speaking. Regarding online learning reviews, online learning is one of the alternative solutions for the learning process, including for students and teachers, during the COVID-19 pandemic. Although it raises some problems, for teachers and students, all parties must be ready to implement it. So that online learning has positive and negative impacts.